1995
DOI: 10.1002/1097-0142(19950501)75:9<2313::aid-cncr2820750921>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hyperbaric oxygen as a chemosensitizer in the treatment of epithelial ovarian cancer in xenografts in mice

Abstract: Background. Resistance to chemotherapy is common in bulky hypoxic tumors such as epithelial ovarian cancer. Hyperbaric oxygen (HBO) oxygenates hypoxic tissues and promotes neovascularization. These unique properties of HBO may help overcome chemotherapy resistance by increasing both tumor perfusion and cellular sensitivity. This study was undertaken to determine if HBO increases the response of epithelial ovarian cancer to cisplatin chemotherapy. Methods. In Phase I, 64 nu/nu mice were divided into four groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…The relatively high levels of oxygen deliverable under HBO exposure make this approach attractive. Several studies in experimental animal tumors have shown that HBO reduces the radioresistance of certain types of tumors [6][7][8][9] and enhances the anticancer activity of doxorubicin and other alkylating agents. 10,11 Clinical trials have been initiated to study the effect of HBO inhalation on the radiotherapy for many types of malignant tumors.…”
Section: Introductionmentioning
confidence: 99%
“…The relatively high levels of oxygen deliverable under HBO exposure make this approach attractive. Several studies in experimental animal tumors have shown that HBO reduces the radioresistance of certain types of tumors [6][7][8][9] and enhances the anticancer activity of doxorubicin and other alkylating agents. 10,11 Clinical trials have been initiated to study the effect of HBO inhalation on the radiotherapy for many types of malignant tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Because of this, HBO has previously been used to enhance the pO 2 in hypoxic tumor tissue, to potentiate the effect of radio- and photo-therapy in both clinical and preclinical trials and also the effect of some forms of chemotherapy like doxorubicin, alkylating agents and 5FU [13-16]. This effect has been ascribed as increased cytotoxicity of the tumor cells to the chemotherapeutic drug in vitro [16,17] and enhanced neovascularisation in vivo [18]. However, recent studies have shown reduced vascularisation after HBO treatment in vivo [19-21].…”
Section: Introductionmentioning
confidence: 99%
“…[40] Daily HBO administration in mice not only does not reduce the therapeutic effect of weekly cisplatin on the bulky hypoxic tumors of epithelial ovarian cancer, but it also enhances the response to chemotherapy, which is likely due to increased tumoral vascularity. [41] Similarly, it has been determined that O(2/3) gas mixture has a direct anti-tumoral effect on human neuroblastoma cell lines, and that the combined O(2/3) and cisplatin treatment produces a stronger cell inhibitory effect compared to when cisplatin is used alone, which is attributed to the cell growth inhibition effect of oxygen therapy. [42] Nevertheless, it seems that the exact effect of oxygen pretreatment on therapeutic effects of chemotherapeutic agents has not been studied comprehensively and needs to be done.…”
mentioning
confidence: 99%